Survey of Greek e-Government services and assessment for SMEs. (21st September 2009) - Tzoumis, Vassilios; Manouselis, Nikos; Patrikakis, Charalampos Z.
The objective of this paper is the analysis and evaluation of e-Government (e-Gov) Services for Small And Medium Enterprises (SMEs). For this purpose, a survey for e-Gov services in Greece is carried out. The analysis and the classification of a sample of 56 e-Gov services is based on e-Government Metadata Standard (e-GMS) for SMEs, through the representation of their characteristics according to specific dimensions. Furthermore, the importance and the relevance of e-Gov services for the business operation are examined, while all services are classified according to SMEs' needs. Through this analysis, conclusions about the existence and relevance of Greek e-Gov services for SMEs are made. In addition, future improvements for the evolution of e-Gov services in Greece are proposed.